ASPEK LINGUISTIK DAN KEBERTERIMAAN DALAM PENERJEMAHAN - Raja Rachmawati (Madah: Jurnal Bahasa dan Sastra, 2014)
Translation does not only deal with language problems but also cultural problems. There are transferring language and culture in translation. Some aspects needs more attention in translation such as linguistics aspects which involve phonology, morphology, syntax, semantics, pragmatics, sociolinguistics, and psycholinguistics. These aspects are able to give a strong basic for a translator to be a good translator. Another aspect that is also important is about form and meaning aspects. Meaning may appeared from various aspects such as the structure of languages, the situation of using language, and the social and culture of languages. The equivalence problems in target language are able to be coped with by giving definition, elaboration, or giving the explanation to the words. A translator should be able to process his translation well in the and a translator also should consider linguistics aspect, acceptability aspects, and politeness. High and low acceptability rate is also influenced by elaborating translator politeness  in the translation.  Penerjemahan bukan sekadar persoalan bahasa, tetapi juga menyangkut masalah budaya. Terdapat alih bahasa dan budaya dalam penerjemahan. Beberapa aspek perlu mendapat perhatian dalam penerjemahan seperti aspek-aspek linguistik yang mencakup fonologi, morfologi, sintaksis, semantik, pragmatik, sosilinguistik, dan psikolinguistik. Aspek-aspek ini dapat memberikan dasar yang kuat bagi seorang ahli bahasa agar dapat menjadi penerjemah yang baik. Hal yang perlu mendapat perhatian adalah unsur bentuk dan makna. Makna bisa ditimbulkan dalam berbagai konteks, makna bisa muncul karena struktur bahasa, situasi penggunaan bahasa, dan sosio-kultur budaya. Masalah keterpadanan makna dalam bahasa sasaran dapat diselesaikan dengan menempuh cara memberikan definisi, elaborasi, atau menerangkan kata-kata tersebut. Penerjemah harus mengolah hasil terjemahannya dengan baik dalam proses penerjemahan. Penerjemah juga  harus mempertimbangkan aspek-aspek linguistik, aspek keberterimaan, dan kesantunan berbahasa. Tinggi rendahnya nilai keberterimaan juga dipengaruhi oleh kesantunan berbahasa penerjemah dalam menguraikan hasil terjemahan.